Feasibility and efficacy of the 2.5 L and 3.8 L impella percutaneous left ventricular support device during high‐risk, percutaneous coronary intervention in patients with severe aortic stenosis. Issue 6 (31st January 2014) - Spiro, Jon; Venugopal, Vinod; Raja, Yogesh; Ludman, Peter F.; Townend, Jonathan N.; Doshi, Sagar N.
<x xml:space="preserve">Abstract</x> Objective Assessment of the feasibility and outcomes of the 2.5 L and 3.8 L Impella cardiac pump in patients with severe aortic stenosis (AS) and left ventricular impairment undergoing percutaneous revascularization (PCI) with or without balloon aortic valvuloplasty (BAV). Methods We reviewed the clinical and procedural findings from a consecutive series of unselected patients with severe AS who underwent PCI during Impella support. In addition, we describe novel "balloon‐assist" techniques that allowed implantation of Impella into the left ventricle (LV) when initial unassisted attempts failed. Results Five patients with severe AS were identified (four males, age 78.2 years, aortic valve area (AVA) 0.6 cm2, left ventricular ejection fraction (LVEF) 24 ± 5%, mean Society of Thoracic Surgeons (STS) mortality 11% (range 3–17%)). The Impella catheter traversed the aortic valve (AV) unassisted in only one patient, with four cases requiring balloon‐assist techniques. All patients underwent planned revascularisation; mean procedure time 177 min (range 135–252 min), mean number of stents 3.4 (range 1–8), with three patients requiring rotational atherectomy. All procedures were well tolerated, with absence of arrhythmia, hypotension, pulmonary edema, stroke, or myocardial infarction. One patient died 48 hr post‐PCI of multi‐organ failure. The four remaining patients were well at 30 days. Conclusion Implantation of the 2.5 and 3.8 L Impella appears feasible in patients with severe AS and left ventricle (LV) impairment. A balloon‐assist technique may be used to facilitate device implantation when initial unassisted attempts fail. Improved hemodynamic stability may enhance the tolerability of lengthy and complex procedures. © 2014 Wiley Periodicals, Inc. © 2014 Wiley Periodicals, Inc.